The correct answer is 3x+90=180
<em>Because you add the 2x and the x and you get 3x then there is a 90 degree angles so you add that and =180</em>
<em>Once you put it in the equation you can subtract 90 from 180 and you get 90 which you then divided by 3x and x equals 30</em>
<em />
<em />
<span>-49 + -2x + 12x = 101 + -12x + 12x Combine like terms: -2x + 12x = 10x -49 + 10x ... 101 + 49 = 150 10x = 150 Divide each side by '10'. x = 15 Simplifying x = 15 </span><span>
</span>
Answer:
Its the first one Guys
Step-by-step explanation:
I hope that helped :)
Answer:
Step-by-step explanation:
As it is a second order equation, it means that it has two possible answers and they are
and
.
The famous quadratic formula for solving any second order equation is the following:
![x_{1} = \frac{-b + \sqrt{b^2 - 4 ac}}{2a}\\x_{2}=\frac{-b - \sqrt{b^2 - 4 ac}}{2a}](https://tex.z-dn.net/?f=x_%7B1%7D%20%3D%20%5Cfrac%7B-b%20%2B%20%5Csqrt%7Bb%5E2%20-%204%20ac%7D%7D%7B2a%7D%5C%5Cx_%7B2%7D%3D%5Cfrac%7B-b%20-%20%5Csqrt%7Bb%5E2%20-%204%20ac%7D%7D%7B2a%7D)
Where a is the coefficient of
, b is the coefficient of x, and c is the free term. In other words,
![a = 3\\b=4\\c=-2](https://tex.z-dn.net/?f=a%20%3D%203%5C%5Cb%3D4%5C%5Cc%3D-2)
as the equation should be in the following form:
![a x^2 + bx+c = 0](https://tex.z-dn.net/?f=a%20x%5E2%20%2B%20bx%2Bc%20%3D%200)
Therefore the possible answer should be the following,
![\frac{-4 + \sqrt{4^2 - 4*3*(-2)}}{2*3}=\frac{-4 +\sqrt{16 + 24}}{6} =\frac{-4 + \sqrt{40}}{6}=\\ \frac{-4 + \sqrt{4*10}}{6} = \frac{-4 + 2\sqrt{10}}{6}](https://tex.z-dn.net/?f=%5Cfrac%7B-4%20%2B%20%5Csqrt%7B4%5E2%20-%204%2A3%2A%28-2%29%7D%7D%7B2%2A3%7D%3D%5Cfrac%7B-4%20%2B%5Csqrt%7B16%20%2B%2024%7D%7D%7B6%7D%20%3D%5Cfrac%7B-4%20%2B%20%5Csqrt%7B40%7D%7D%7B6%7D%3D%5C%5C%20%5Cfrac%7B-4%20%2B%20%5Csqrt%7B4%2A10%7D%7D%7B6%7D%20%3D%20%5Cfrac%7B-4%20%2B%202%5Csqrt%7B10%7D%7D%7B6%7D)
![\frac{2*(-2 + \sqrt{10})}{2*3} = \frac{-2 + \sqrt{10}}{3}](https://tex.z-dn.net/?f=%5Cfrac%7B2%2A%28-2%20%2B%20%5Csqrt%7B10%7D%29%7D%7B2%2A3%7D%20%3D%20%5Cfrac%7B-2%20%2B%20%5Csqrt%7B10%7D%7D%7B3%7D)
by dividing the numerator and denominator by 2, we can deduce the following,
Answer: h - 5
Step-by-step explanation:
h decreased by 5
h - 5
I'm sorry TnT I don't really know how to explain this but I'm 100% sure my answer is correct. Hope it helped!